Pengaruh Inovasi Produk dan Kualitas Produk terhadap Minat Beli Konsumen Donat Chani Kabupaten Tasikmalaya - Moh Rizal Ramli; Ardhiansyah Ardhiansyah; Rina Madyasari; Alfin Nur Arifah (BISMA : Business and Management Journal, 2026)
Increasing competition in the culinary Micro, Small, and Medium Enterprises (MSMEs) sector requires businesses to enhance their competitiveness through product innovation and product quality to stimulate consumers' purchase intention. This study aims to examine the effects of product innovation and product quality on consumers' purchase intention at Donat Chani MSME in Sukarame District, Tasikmalaya Regency. The study employed a quantitative approach using descriptive and verificative methods. Data were collected through questionnaires distributed to 100 respondents selected using purposive sampling and were analyzed using multiple linear regression with IBM SPSS Statistics version 27. The results indicate that both product innovation and product quality have a positive and significant effect on consumers' purchase intention. Product innovation has a regression coefficient of 0.453, while product quality has a regression coefficient of 0.292. The coefficient of determination (R²) of 0.498 indicates that these two variables explain 49.8% of the variance in consumers' purchase intention. The study concludes that improving product innovation and maintaining high product quality can significantly enhance consumers' purchase intention. The findings imply that MSMEs should continuously develop product variations, maintain consistent product quality, and implement marketing strategies that align with consumers' needs and preferences.